Socio-cultural adaptation of Malaysian graduates in South Korea under look east policy human capital development program / Nabila Huda Ibrahim, Keum Hyun Kim and Seung Yoan Rou - Ibrahim, Nabila Huda; Keum, Hyun Kim; Seung, Yoan Rou (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2023)
The relevance of the Look East Policy (LEP) after four decades indicates the success in producing the desired human capital with positive values emulated by both South Korea and Japan. This study examines the experience of LEP participants as sojourners during their stay in South Korea for their first degree. Through a qualitative study, LEP participants shared their experiences and insights into their socio-cultural adjustment. The results indicate that LEP participants were successfully emulated and practiced Korean culture. They managed to overcome challenges in adaptation, such as language, environment, and cultural differences. They demonstrate internalization of Korean culture and practice in their professional and personal life. The findings indicate the positive outcome of LEP program for human capital development as participants have been practicing these values and culture that they learnt from Korea.